2019
DOI: 10.1039/c9dt02476j
|View full text |Cite
|
Sign up to set email alerts
|

Spin state solvomorphism in a series of rare S = 1 manganese(iii) complexes

Abstract: Structural, magnetic and spectroscopic data on four new spin triplet Mn3+ complexes reveals a large magnetic anisotropy. Spin state is sensitive to lattice contents as the spin quintet ground state is stabilized on co-crystallization with ethanol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 46 publications
2
24
1
Order By: Relevance
“…In contrast, Mn 3+ , which is also a non-Kramers ion and for which thermal SCO is now well-established, 30 , 31 , 66 71 switches between the fully unpaired spin quintet and partially paired spin triplet forms; therefore, a considerable ZFS is expected to persist at low temperature. Spin triplet Mn 3+ is generally not common, with about 20 examples at room temperature, 32 , 72 − 88 and the ZFS interactions have been quantified via the D and E parameters in just two cases. 32 , 83 These studies have however demonstrated that spin triplet Mn 3+ has the highest ZFS parameters for any manganese ion, with D values in the range +15 to +20 cm –1 , 65 while the axially elongated spin quintet form shows small but negative values in the range of −4.5 to −1.2 cm –1 with only a small number of published spin quintet Mn 3+ examples with positive D values, i.e., axial compression of the Jahn–Teller ion.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Mn 3+ , which is also a non-Kramers ion and for which thermal SCO is now well-established, 30 , 31 , 66 71 switches between the fully unpaired spin quintet and partially paired spin triplet forms; therefore, a considerable ZFS is expected to persist at low temperature. Spin triplet Mn 3+ is generally not common, with about 20 examples at room temperature, 32 , 72 − 88 and the ZFS interactions have been quantified via the D and E parameters in just two cases. 32 , 83 These studies have however demonstrated that spin triplet Mn 3+ has the highest ZFS parameters for any manganese ion, with D values in the range +15 to +20 cm –1 , 65 while the axially elongated spin quintet form shows small but negative values in the range of −4.5 to −1.2 cm –1 with only a small number of published spin quintet Mn 3+ examples with positive D values, i.e., axial compression of the Jahn–Teller ion.…”
Section: Introductionmentioning
confidence: 99%
“…The simulation yielded the following spin Hamiltonian parameters g x =2.08(5), g y =2.10(5), g z =2.15(5), D =+7.7(1) cm −1 and E / D =+0.026 (Figure S5) in reasonable agreement with the magnetic susceptibility results. According to high‐field EPR spectroscopy, low‐spin manganese(III) complexes with N 4 O 2 donor or two N 3 scorpionato ligands exhibit a larger zero‐field splitting with D =+19.6/+17.97/ +15.89 cm −1 and E / D =+0.103/+0.023/+0.003 …”
Section: Methodsmentioning
confidence: 99%
“…Hydrogen-bonding is a particularly effective tool in modulating SCO and this approach was successfully used to generate an extended homochiral 2D sheet of mixed valence Fe 2+ /Fe 3+ sites, which exhibited SCO and light induced excited spin state trapping (LIESST) [36]. In our own work with the [Mn(R-sal 2 323)] + series of Schiff base complexes, we have established that thermal SCO is possible in the less studied d 4 ion Mn 3+ [37][38][39][40][41][42][43][44][45][46]. The hexadentate ligand type used in this approach results from condensation of 1,2-bis(3-aminopropylamino)ethane with a substituted 2-hydroxybenzaldehyde, and the ligand series may be abbreviated as R-Sal 2 323 to indicate the 323 alkyl connectivity in the starting tetraamine and the substitution (R) on the phenolate ring.…”
Section: Introductionmentioning
confidence: 92%
“…Complexes ( 1) and (2) crystallize isostructurally in monoclinic space group P2 1 /c with Z = 4 where the asymmetric unit contains a full [MnL 1 ] + cation and one full triflate or one full hexafluorophosphate anion, respectively, Figure 2. The hexadentate Schiff base ligand chelates the Mn 3+ centre in pseudo octahedral geometry with two trans-phenolate donors, O1 and O3, two cis-amine and two cis-imine donor atoms, in the same way as previously observed for manganese complexes with this ligand type [37][38][39][40][41][42][43][44][45][46]48]. Residual electron density in both data sets was modelled as part occupancy water molecules using Platon SQUEEZE [47].…”
Section: Structural Characterisation Of Compounds (1)-(3)mentioning
confidence: 99%
See 1 more Smart Citation